2015
DOI: 10.3892/etm.2015.2593
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone is an effective treatment for patients with post-stroke depression combined with type 2 diabetes mellitus

Abstract: The antidepressive effects of the antidiabetic medicine, pioglitazone, were recently reported in several studies. These effects may ameliorate the depressive symptoms of patients with post-stroke depression (PSD). The present study aimed to evaluate the antidepressive effect of pioglitazone in patients with PSD combined with type 2 diabetes. A total of 118 consecutive patients with stroke who had depression were studied for an average of 3 months. The Diagnostic and Statistical Manual of Mental Disorders (four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
(12 reference statements)
0
28
0
Order By: Relevance
“…Three trials of metformin used active controls. In the two aforementioned RCT's against pioglitazone, metformin was inferior in reducing depressive symptoms in patients with depression (Hu et al, 2015;Kashani et al, 2013). In a 12-week trial of women with polycystic ovarian syndrome, myo-inositol was marginally superior to metformin in reducing depressive symptoms.…”
Section: Non-randomised Trialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Three trials of metformin used active controls. In the two aforementioned RCT's against pioglitazone, metformin was inferior in reducing depressive symptoms in patients with depression (Hu et al, 2015;Kashani et al, 2013). In a 12-week trial of women with polycystic ovarian syndrome, myo-inositol was marginally superior to metformin in reducing depressive symptoms.…”
Section: Non-randomised Trialsmentioning
confidence: 98%
“…Of the 8 RCTs testing pioglitazone, 6 were placebo-controlled (Calabrese, 2017;Lin et al, 2015;Roohafza et al, 2014;Sepanjnia et al, 2012;Simuni T., 2015;Zeinoddini et al, 2015) and two used metformin as a control (Hu et al, 2015;Kashani et al, 2013). Apart from one study (Lin et al, 2015), all RCTs selecting depressed patients at baseline reported significant reduction in depressive symptoms compared to controls.…”
Section: Randomised Controlled Trialsmentioning
confidence: 99%
“…Non-SSRI antidepressants have not been widely studied in stroke, but drugs like agomelatine may be particularly attractive given that melatonin decreases central nervous system inflammation [107] and improves outcome in experimental models of cerebral ischemia [108,109]. Additional evidence for the role of inflammation in the genesis of PSD and as a viable target for the treatment of PSD includes the fact that treatment with pioglitazone, as opposed to metformin, decreases PSD in patients with diabetes [110]. Peroxisome proliferator-activated receptor-γ agonists like pioglitazone have both anti-inflammatory and neuroprotective properties [111,112].…”
Section: Therapeutic Approaches To the Treatment Of Depression: A Focmentioning
confidence: 99%
“…In the 4 prospective open-label studies [34][35][36][37] (▶ table 1), 118 patients with a current MDE and metabolic disorders were assessed before the beginning and after 8 or 12 weeks of treatment with PPAR-γ agonists (pioglitazone or rosiglitazone) and 59 by metformin. For rosiglitazone [34], the starting dose, 4 mg/d, was increased after 4 weeks at 8 mg/d.…”
Section: Efficacymentioning
confidence: 99%